2017
DOI: 10.1002/cncy.21880
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of glass slides and various digital‐slide modalities for cytopathology screening and interpretation

Abstract: The Aperio whole-slide scanner with 1 z-plane scanning and the Panoptiq imaging system with z-stacking are both suitable for cytopathology screening and interpretation. However, ROI z-stacks do offer a superior mechanism for overcoming focusing problems commonly encountered with digital cytology slides. Unlike whole-slide imaging, the acquisition of representative z-stack images with the Panoptiq system requires a trained cytologist to create digital files. Cancer Cytopathol 2017;125:701-9. © 2017 American Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 12 publications
(18 reference statements)
3
67
0
Order By: Relevance
“…Higher intraobserver agreement was seen with cervical smears (Table ), approaching or even exceeding crude intraobserver agreement (85.6%) and intraobserver kappa scores (ranging from 0.47 to 0.81) reported in the literature for cervical‐vaginal smears . The greatest concordance and diagnostic accuracy would be expected using digital whole slide imaging for cytology specimens; one study showed 90%‐100% concordance between Aperio digital images and glass slides for thirty cases (10 ThinPrep gynecologic cases plus 20 nongynecologic cases) …”
Section: International Telecytology Studies: How Do They Compare To Amentioning
confidence: 82%
See 1 more Smart Citation
“…Higher intraobserver agreement was seen with cervical smears (Table ), approaching or even exceeding crude intraobserver agreement (85.6%) and intraobserver kappa scores (ranging from 0.47 to 0.81) reported in the literature for cervical‐vaginal smears . The greatest concordance and diagnostic accuracy would be expected using digital whole slide imaging for cytology specimens; one study showed 90%‐100% concordance between Aperio digital images and glass slides for thirty cases (10 ThinPrep gynecologic cases plus 20 nongynecologic cases) …”
Section: International Telecytology Studies: How Do They Compare To Amentioning
confidence: 82%
“…For 3‐dimensional groups, the plane of focus is very important, and automated scanners often produce images that are out of focus. An important solution to this problem has been the development of high magnification z‐axis image stacking, in which glass slides are scanned in multiple image planes along the z‐axis, resulting in a composite image of individual scans stacked on top of each other (a z‐stack) . Z‐stacking results in images that can be viewed at different planes, and allows for better focus of 3‐dimensional groups and improved visualization of individual cells.…”
Section: Overview Of Telecytologymentioning
confidence: 99%
“…FDA approved telepathology systems, used for screening, primary diagnosis, second opinion, and education, can be designed as a static mode (images are captured, transmitted, and then viewed at distance), dynamic mode (live video images are transmitted and viewed at distance in real time), or dynamic robotic mode (when the viewer controls the microscope at the originating site) [17,18]. The practice of telepathology has been validated in surgical pathology (frozen section) and cytology [19,20 ▪▪ ,2123], however, in renal pathology it is currently under testing. The two major indications that best fit the use of telepathology are assessment of adequacy of tissue procurement at the time of the renal biopsy (currently under validation at the University of Miami), and adequacy of renal parenchyma from frozen sections prior to transplantation.…”
Section: Virtual Microscopy In Clinical Practicementioning
confidence: 99%
“…Of the 100 cases scanned, 4 contained corrupted data caused by z-stacks that were not fully embedded on the main scan and therefore these cases were excluded from further analysis. The average data size per case of the 96 cases was 226 megabytes (range, 64.4-483.4 megabytes), the average number of focal 320 scans per case was 4.2 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], and the mean number of embedded z-stacks per case was 6.15 (range, 0-14). The average image scanning time was 4.36 minutes per slide (range, 3:11-7:03 minutes per slide).…”
Section: Digital Cytology Case Analysismentioning
confidence: 99%